Business & product development of a customer loyalty platform - Yeh, Raymond Jing Xiang (2017)
The aim of the project is to document the process of starting up a technology company from business conceptualisation to the deployment of an enterprise ready application on relevant cloud infrastructure. The program will be aplatform for businesses to manage their customer loyalty program. It features an easy-to-sign-up process using only the customers' emails, allowing businesses to capture customer information with low bounce rate. Besides application development, the project will explore concepts such as virtualisation, load balancing and auto scaling to create an enterprise ready environment for the application.